1994
DOI: 10.1021/j100059a012
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Spectrum and Structure of Methylcyclopropane.cntdot.HCl

Abstract: The microwave spectrum of the methylcyclopropane-HC1 (MCP.HC1) complex has been observed using a pulsed nozzle, molecular beam Fourier transform microwave spectrometer. Transitions were assigned with the aid of the quadrupole hyperfine structure from the chlorine nucleus. The rotational constants of the C~H T H~~C~ speciesareA =6408.1(2) M H z , B = 1410.486(1) M H z , a n d C = 1224.155(1) MHz. Inadditiontothisspecies, the spectra of the MCP-H3'C1 and MCP.D3T1 isotopomers have also been studied. The data are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1998
1998
2001
2001

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…Our high-level molecular orbital (MO) calculations provide strong support for the formation of a weak and non-conventional complex of cyclopropane-ammonia which has been found experimentally [9]. In this complex the ammonia umbrella is pointed up, stacked onto the ring of cyclopropane and the hydrogen atoms prefer a staggered arrangement, and the whole complex is found to be stable.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Our high-level molecular orbital (MO) calculations provide strong support for the formation of a weak and non-conventional complex of cyclopropane-ammonia which has been found experimentally [9]. In this complex the ammonia umbrella is pointed up, stacked onto the ring of cyclopropane and the hydrogen atoms prefer a staggered arrangement, and the whole complex is found to be stable.…”
Section: Discussionsupporting
confidence: 72%
“…These structures are found to be less stable than those where ammonia acts as a proton acceptor. Forest and Kuczkowski [9] investigated the C 3 H 6 ..NH 3 complex experimentally using Fourier Transform Microwave (FTMW) spectroscopy and showed that the ammonia molecule acts as a proton acceptor. The R CM..N is found to be in good agreement with their value (3.66 A Ê ) for the staggered confomer.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following Truscott et al, we will refer to this isomer as the asymmetric complex. The complex of methylcyclopropane with HCl has also been investigated by Forest et al, who report on pulsed nozzle Fourier transform microwave spectroscopy, supported by theoretical calculations. Their distributed multipole electrostatic calculations suggest that the symmetric isomer, in which HCl interacts with the C−C bond opposite to the methyl substituent, should be more stable, by approximately 0.6 kJ mol -1 , than the asymmetric complex.…”
Section: Introductionmentioning
confidence: 85%